A study to evaluate the indications for performing skin biopsies - Balasubramanian, Pradeep; Anil, Anjali J. (International Journal of Research in Dermatology, 2020)
Background: The skin biopsy is an invaluable tool done for the confirmation of several skin disorders. Skin biopsy serves as an indispensable tool in the diagnosis of skin disorders especially for the clinical presentation which has several differential diagnoses or diagnostic difficulties. The studies to determine the indications for which skin biopsy is routinely performed are few. Hence, we conducted this study. Methods: We assessed the biopsy request forms of two consecutive years (from January 2017 to December 2018) to evaluate the indications for which the biopsies were performed. The statistical data were expressed as number and percentage. Results: In the present study, 320 consecutive skin biopsy request forms were evaluated for the indications for performing skin biopsy. In the present study, the skin biopsy was done predominantly for the spongiotic disorders followed by granulomatous and psoriasiform disorders. Among the granulomatous disorders, skin biopsy was done commonly in case of Hansen’s disease. In our study incisional biopsy was the technique often used followed by excisional and punch biopsy. Conclusions: The common indications for which the skin biopsies were performed was determined in this study. This study bridges the gap since the studies performed in this aspect are lacking.